2012
DOI: 10.1016/j.injury.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Early fasciotomy in patients with extremity vascular injury is associated with decreased risk of adverse limb outcomes: A review of the National Trauma Data Bank

Abstract: Introduction and Objectives Lower Extremity (LE) arterial trauma and its treatment may lead to extremity compartment syndrome (ECS). In that setting, the decision to perform fasciotomies is multifactoral and is not well delineated. We evaluated the outcomes of patients with surgically treated LE arterial injury who underwent early or delayed fasciotomies. Methods The National Trauma Data Bank (NTDB) was retrospectively reviewed for patients who had LE arterial trauma and underwent both open vascular repair a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(73 citation statements)
references
References 22 publications
4
62
0
7
Order By: Relevance
“…Liberal fasciotomy should be applied prophylactically to reduce risk of adverse limb outcomes [24]. Patients who underwent delayed fasciotomies had twice the rate of major amputation and a threefold higher mortality [22].…”
Section: Discussionmentioning
confidence: 99%
“…Liberal fasciotomy should be applied prophylactically to reduce risk of adverse limb outcomes [24]. Patients who underwent delayed fasciotomies had twice the rate of major amputation and a threefold higher mortality [22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fasciotomy needs to be performed to reduce the risk of limb loss and death. 3 Many factors, such as the extent of soft tissue damage, the capacity of collaterals, pre-existing arterial disease, and the ischemia time may affect the clinical outcomes. 6 Mckenzie et al 7 found that the greatest impact on decision making between limb salvage and amputation depend on the severity of soft tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…2 In addition, the presence of extremity compartment syndrome in vascular injury is associated with significant morbidity and mortality. 3 Our case was unique since the patient had delayed revascularization for 42 hours with compartment syndrome as a comorbid condition yet successfully underwent arterial repair surgery without serious complication. …”
Section: Introductionmentioning
confidence: 93%
“…53 Fasciotomies should be performed in a timely fashion when evidence of elevated compartment pressures is present. 54,55 …”
Section: S a M E S T U D Y S H O W E D T H A T P A T I E N T S U N D mentioning
confidence: 99%